Analysis of Changes in Agricultural Land Area in Central Lombok Regency Using Google Earth Engine - Ulatalita, Nabila Anzela; Fatanaya, Nafika; Ulfa, Kurnia; Robbaniyyah, Nuzla Af'idatur; Alfian, Muhammad Rijal (Semeton Mathematics Journal, 2025)
Agricultural land plays a vital role in supporting food security and the regional economy; however, rapid development often leads to land-use conversion. This study aims to analyze changes in agricultural land in Central Lombok Regency over the past ten years (2014–2023) using the Google Earth Engine (GEE) platform. The research utilized Landsat satellite imagery to classify land cover types and identify agricultural areas through supervised classification and change detection techniques. The analysis results show a significant decline in agricultural land area, from 29% in 2014 to 26% in 2023. This decrease indicates a conversion of agricultural land to other more economically profitable uses, such as infrastructure development and plantation expansion. The accuracy assessment yielded an overall accuracy of 99%, which is categorized as very good, demonstrating the reliability of the model in mapping land-use changes. The findings of this study are expected to provide useful insights for policymakers in promoting sustainable land-use planning and mitigating the negative impacts of land conversion on the agricultural sector in Central Lombok Regency.